Hybrid mathematical modeling and multi‐objective optimization of mechanical properties of green composites based on starch and modified rice straw fillers. Issue 36 (24th April 2021) - Shoja, Maryam; Kazemi, Reza; Mohammadi‐Roshandeh, Jamshid; Farizeh, Tara; Shadman, Alireza; Hemmati, Farkhondeh
Abstract: A hybrid mathematical modeling/optimization approach based on the response surface methodology (RSM) and desirability function (DF) capabilities was applied here to imitate and optimize the mechanical properties of thermoplastic starch‐based biocomposites. In order to prepare the biodegradable and renewable biocomposites, rice straw (RS) was chemically modified to obtain more effective sustainable reinforcing fillers for starch, having semi‐thermoset and core‐shell structures. A combination of different RS products was used in the biocomposites and the composition of RS‐based fillers was chosen as control variable. A series of experiments, by using RSM, were designed to assess the effects of filler loading and composition on the Young modulus, tensile strength, ultimate strain, and absorbed energy of the biocomposites. The best‐fitting regression functions were identified via RSM statistical analysis and transformed into DF to optimize the desired responses concurrently. The findings demonstrate that the starch/RS product biocomposites with optimum elastic modulus (339.3 MPa), tensile strength (9.8 MPa), elongation at break (13.8%), and absorbed energy (1831.2 kJ/m 2 ) were obtained by incorporating RS‐based fillers with both semi‐thermoset and core‐shell structures in combination with each other at loadings of 13.5 and 6.5 phr, respectively. Abstract : All mechanical characteristics of starch/treated rice straw (RS) biocomposites, such as toughness, elastic modulus and tensile strength, have been mathematically modelled and simultaneously optimized by using the capabilities of response surface methodology and desirability function. The experimental design and mathematical modeling were carried out to design the starch/RS‐based biocomposites. A combination of chemically‐modified RS fillers with semi‐thermoset, thermoplastic and core‐shell structures was applied to obtain the starch‐based biocomposites..